2016
DOI: 10.1097/md.0000000000003527
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metformin Use With Cancer-Specific Mortality in Hepatocellular Carcinoma After Curative Resection

Abstract: Many preclinical reports and retrospective population studies have shown an anticancer effect of metformin in patients with several types of cancer and comorbid type 2 diabetes mellitus (T2DM). In this work, the anticancer effect of metformin was assessed in hepatocellular carcinoma (HCC) patients with T2DM who underwent curative resection.A population-based retrospective cohort design was used. Data were obtained from the National Health Insurance Service and Korea Center Cancer Registry in the Republic of Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…So far, some observational studies have already suggested that metformin use might have antitumoural effects against HCC in specific subgroups. In line with our observation, metformin treatment was associated with reduced tumour recurrence and improvement of OS in patients who underwent hepatic resection for HCC . Another retrospective study in patients undergoing LT for HCC could show that OS was improved in patients receiving sirolimus and metformin .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…So far, some observational studies have already suggested that metformin use might have antitumoural effects against HCC in specific subgroups. In line with our observation, metformin treatment was associated with reduced tumour recurrence and improvement of OS in patients who underwent hepatic resection for HCC . Another retrospective study in patients undergoing LT for HCC could show that OS was improved in patients receiving sirolimus and metformin .…”
Section: Discussionsupporting
confidence: 88%
“…In line with our observation, metformin treatment was associated with reduced tumour recurrence and improvement of OS in patients who underwent hepatic resection for HCC. [14][15][16][17] Another retrospective study in patients undergoing LT for HCC could show that OS was improved in patients receiving sirolimus and metformin. 18 In a small propensity score matched cohort of 76 patients receiving radiotherapy for HCC, medication with metformin was also associated with a prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…143 Population studies such as that of Seo et al have shown that diabetic patients treated with metformin, which inhibits ETC Complex I, present an approximately 30% reduced overall cancer incidence and mortality rate. 144 Therefore, mitochondrial-targeted therapeutics are emerging as an exciting opportunity for cancer therapy.…”
Section: Mitochondrial Targeting By Potential Therapeuticsmentioning
confidence: 99%
“…Patients taking metformin display approximately 30% reduced overall cancer incidence as well as cancer mortality. 10 However, the mechanisms of metformin on cancers have still not fully understood. A number of studies suggest that the inhibition of metformin on cancer cells might associate with its activity of targeting cellular mitochondria.…”
Section: Introductionmentioning
confidence: 99%